“Mulher é muito difícil”: o (des)amparo público e religioso das dependentes químicas na cracolândia de São Paulo - Trigo, Ana (2022)
Misery and exclusion are part drug addicts lives in cracolândia, heart of São Paulo downtown daily. For the researched women’s group studied in this thesis, the situation is aggravated by the stigmas that mark female drug users. Over the years, successive governments have turned cracolândia into a laboratory of assistance programs that are characterized by a lack of continuity including repressive actions with more media coverage than effective results. In a place so neglected by governments, religion is taking over through agreements with social organizations and therapeutic communities, mostly of them religious. This thesis aims to investigate the impact of the services offered to the female population that suffers from drug addiction. Therefore, the field research was carried out with public and religious groups that serve women in cracolândia. The chosen methodology was qualitative, with participant observation and open interviews carried out with hosted women, volunteers, missionaries, and care professionals. The hypotheses presented in this work are that drug adict women are more stigmatized than men because they are judged by their behavior; the available service models are aimed at the male audience; and the religious groups that work in cracolândia, at the same time that they welcome women who are addicted to crack and other substances, they potentiate the stigmas